A Security of Cloud Data Storage Using AF Crawler Algorithm in Cloud Computing Systems - Sheeba Pershi, N; Sathish Kumar, G (International Journal of Computer Sciences and Engineering, 2025)
Gradually more furthermore, more associations are opting for outsourcing information to remote cloud administration providers (CSPs). clients can rent the CSPs capacity foundation to store furthermore, get back almost limitless sum of information by paying sum per month. On behalf of an improved level of scalability, availability, furthermore, durability, some clients may want their information to be virtual on distinctive servers over distinctive information centers. The more duplicates the CSP is asked to store, the more sum the clients are charged. As a result, clients need to have a solid assurance that the CSP is storing all information duplicates that are chosen upon in the administration contract, furthermore, all these duplicates are reliable with the most later changes issued by the clients. Map-based provable multi-copy dynamic information ownership (MB-PMDDP) technique is being proposed in this paper furthermore, comprises of the following features: 1) it affords an proof to the clients that the CSP is not degenerate by storing less copies; 2) it bolsters outsourcing of dynamic data, i.e., it bolsters block-level functions, such as square alteration, addition, deletion, furthermore, append; furthermore, 3) it licenses official clients to easily access the record duplicates stored by the CSP. In addition, we discuss the security against conspiring servers, furthermore, discuss how to perceive tainted duplicates by a little revising the projected scheme.